Factors Strengthening the Involvement of Employees and Their Role in Knowledge Management in an Enterprise: An Empirical Evidence from Polish Companies - Rafał DREWNIAK; Robert KARASZEWSKI (Revista de Management Comparat International)
Contemporary conditions in the business environment make increased efforts of companies in the search for the key sources of competitive advantage. One of them is to have employees, who are fully dedicated and committed to the objectives of a company. The degree and scope of this engagement determine the performance, social behaviors and relationships between co-workers, as well as they promote the growth of innovation and improving the financial condition of companies. Therefore, in managing modern enterprises it is important not only to use the appropriate external stimuli to motivate employees, but above all to create conditions that foster their inner motivation. The article attempts to systematize the knowledge of the theory of employee involvement and the factors determining its level as well as to analyze the issue of building the involvement of knowledge workers. The empirical study focused on the identification of instruments used to build employee engagement was applied to achieve the aforementioned research aim. The study involved 86 employees from 4 companies. The study identified a group of key conditions that, in the opinion of employees, significantly affect the degree of their involvement and contribute to the increase in the body of knowledge in the surveyed companies.